Demographic Challenges Facing European Economies in the Age of the Fourth Industrial Revolution - Damyanov, Dimitar (Research Papers, 2018)
Demographic changes are often mentioned as one of the most important and long-lasting trends affecting economic development during the second half of the 20th and the early 21st century. They pose some significant challenges for economic policies, as well as for the individual behaviour of economic agents, especially with the world entering a time of profound technological transformation. This paper reviews the past effects of demographic changes on several aspects of the development of European economies and attempts to make predictions about the future interactions between the two processes.